2017
DOI: 10.1093/labmed/lmx044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fasting on Complete Blood Count Assayed in Capillary Blood Samples

Abstract: Food consumption impacts CBC results. To ensure the consistency, quality, and repeatability of CBC analysis, blood should be drawn from fasting patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…This finding is in line with the reports of Akrami et al [42], Plumelle et al [43] and Turan et al [44] who observed no statistically significant difference between fasting and postprandial levels of these haematological parameters. However, the findings of this study disagrees with the report of Nematy et al [45] who observed higher RBC count following Ramadan fasting and Naderi et al [46], and Koscielnak et al [47] who posited that fasting decreased RBC counts, Hb and HCT.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in line with the reports of Akrami et al [42], Plumelle et al [43] and Turan et al [44] who observed no statistically significant difference between fasting and postprandial levels of these haematological parameters. However, the findings of this study disagrees with the report of Nematy et al [45] who observed higher RBC count following Ramadan fasting and Naderi et al [46], and Koscielnak et al [47] who posited that fasting decreased RBC counts, Hb and HCT.…”
Section: Discussioncontrasting
confidence: 99%
“…The observed differences in leukocytes between schizophrenia patients and healthy controls in the included articles were of small magnitude, comparable to the difference seen throughout a day ( 42 ). Also the fasting status is important when comparing blood cell counts, as neutrophil count has been shown to increase after food intake while lymphocyte count decrease ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following a screening period of up to 5 weeks, subjects were randomized in a 1:1 ratio to one of two treatment sequences [Sandoz proposed biosimilar pegfilgrastim followed by reference pegfilgrastim (EU‐authorized) or reference pegfilgrastim (EU‐authorized) followed by Sandoz proposed biosimilar pegfilgrastim]. Pegfilgrastim (Sandoz proposed biosimilar or reference) was administered as a single 6 mg subcutaneous (SC) injection on Day 1 of each period, following a ≥10‐h fast (to avoid the impact of food consumption on the neutrophil count ), into the SC tissue of the lower abdomen. A follow‐up visit was carried out 28 days after pegfilgrastim administration in each period.…”
Section: Methodsmentioning
confidence: 99%